Co-existence of integumentary lesions and lung x-ray abnormalities in patients with paracoccidioidomycosis (PCM) (2008)
ABSTRACT : In paracoccidioidomycosis (PCM), the primary lung infection remains silent. In this study, attempts weredone to define the primary target organ by correlating lung radiographic abnormalities with the time course of mucosal/skin lesions concurrently exhibited at diagnosis by 63 patients in whom microscopy and/or isolation ofParacoccidioidesbrasiliensisfrom respiratory secretions had been positive. Mucosal and skin lesions were found in 65.1% and 12.7% ofthe patients, respectively. Odynophagia and dysphagia were present in 38.1% each. All patients had lung interstitialinfiltrates, and 31.7% had also alveolar lesions; fibrosis was recorded in 46% of them. An inverse correlation was shownfor fibrosis and presence of either odynophagia or dysphagia. Cluster analyzes strongly supported two sets of patients:those with mucosal damage, odynophagia/dysphagia, and alveolo-interstitial infiltrates and those with dermal lesions,dyspnea, and lung fibrosis. These groups may represent novel stages in the natural course of PCM.